PENGARUH PRICE DISCOUNT DAN BONUS PACK TERHADAP IMPULSE BUYING PADA PELANGGAN ALFAMART KOTA TENGAH KECAMATAN KEPENUHAN - Siska Hastari Utami; Yulfita Aini (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2020)
This study aims to determine: the effect of price discounts and bonus packs on impulse buying on Alfamart customers in Central City, both partially and simultaneously. The study population was buyers at Alfamart. The sampling technique uses accidental sampling technique with 100 respondents. The independent variable in this study is the price discount (X1), bonus pack (X2) and the dependent variable impulse buying (Y). Methods of data collection using field research and library research. Field research consisted of observations, questionnaires and interviews. Data analysis using multiple linear regression analysis using the SPSS program. The results of multiple linear regression analysis obtained by the regression equation Y = 1.081 + 0.628 + 0.598. Partially, t-arithmetic t-price discount 9,358 and bonus pack 8,306. Simultaneously, an F-count of 4219,289 was obtained. The results showed that 98.9% impulse buying was influenced by price discounts and bonus packs, while the remaining 1.1% was influenced by other variables not examined in this study. The conclusion of this study is based on the results of partial testing and simultaneous price discounts and bonus packs have a significant effect on impulse buying.